PERANAN KEJAKSAAN DALAM MELAKUKAN PENUNTUTAN PERKARA TINDAK PIDANA NARKOTIKA - Cardiana Harahap; Chainur Arrasyid; Mahmud Mulyadi; Syafruddin Sulung Hasibuan (USU LAW JOURNAL, 2016)
ABSTRACT A according to Article 30, paragraph 1, letter b of Law on Prosecuting Attorney, a prosecuting attorney, as a public prosecutor, has the authority to exercise prosecution on criminal act cases. In this case, it is especially in narcotics criminal act as it is stipulated in Law on Narcotics and is not separated from criminal justice system. The role of prosecuting attorneys in prosecuting narcotics criminal act perpetrators is by coordinating with the other law enforcement officials, especially BNN officials, the Police, and PPNS officials. Law on Narcotics does not deal with prosecuting attorneys in narcotics cases; they only agree on the beginning of investigation and receive minutes of investigation. The most dominant obstacle is the knowledge of the fact in the field because prosecuting attorneys cannot investigate narcotics cases in the field.It is recommended that prosecuting attorneys do discretion according to the prevailing laws and regulations, break through any regulation by putting forward justice, human rights, and public interest in exercising prosecution of narcotics criminal act cases since narcotics is related to public interest. Law on narcotics should provide authority for prosecuting attorneys to be investigators. Keywords: Role of Prosecuting Attorney, Prosecution, Narcotics Criminal Act